"Getting on the same page" enhancing team performance with shared mental models—case studies of evidence informed practice in elite sport - Ashford, M.; Taylor, J.; Payne, J.; Waldouck, D.; Collins, D. (Frontiers in Sports and Active Living, 2023)
Within high performing, team invasion sports, collective decision making and coordination between teammates are essential characteristics. There is a wealth of evidence supportive of shared mental models as being an important construct to underpin team coordination. Yet, to this point, there is limited research considering the coaches' voices in the application of shared mental models in high performance sport, nor the challenges coaches face throughout the process. Given these limitations, we provide two case studies of evidence informed practice which privilege the voice of coaches who work in elite rugby union. In doing so, we aim to offer a deeper insight regarding the development, implementation, and continued use of shared mental models to enhance performance. Through these first-person case studies, we present the development of two shared mental models and the processes taken, challenges faced, and coaching methods used to underpin them. The case studies are then discussed with implications for coaches' practice supporting the development of their players' collective decision making.